Diagnosis of sepsis in dogs by measuring carbonylated proteins (PCOs) and paraoxonase (PON-1) (International Journal of Health, Animal Science and Food Safety, 2018)
An early diagnosis of sepsis could allow a better prognosis and avoid the abuse of antibiotic administration; unfortunately, in veterinary medicine, specific and sensitive markers of sepsis are not available.Because Protein Carbonyls (PCOs), that result from protein oxidation, are widely used in human medicine as sepsis markers , the aim of our study was to validate an ELISA kit (Enzolifesciences, 3V Chimica, Roma) on canine serum and to measure PCOs, after a preliminary validation study, in three groups (homogeneous for age and size): healthy dogs without clinical or laboratory abnormalities (A, n=14), dogs with septic (B, n=14) and non-septic inflammation (C, n=12) at the first presentation and without previous treatments. Moreover, Paraoxonase-1, a negative acute phase protein with anti-oxidant properties (PON-1) was measured in each group with a method already validated in dogs.A Kruskal-Wallis test followed by a Wilcoxon signed rank test was used to evaluate differences between groups.The ELISA method for measuring PCOs showed a very good precision (coefficient of variation
Keywords: ELISA; Oxidative stress; PCO; PON-1